The Impact of Peer and Teacher Feedback Using Twitter on FFL Writing Class - Wulan Novita Haeriyati; Dudung Gumilar; Dante Darmawangsa (Lectura : Jurnal Pendidikan, 2023)
Feedback is a technique used in the teaching and learning environment to improve the acquisition of knowledge and skills, including writing mastery. This study investigates the impact of incorporating peer and teacher feedback techniques through Twitter on developing writing skills in French as a Foreign Language (FFL) class. The study employed a quantitative experimental approach that adopted a One Group Pre-Test and Post-Test design. A sample of 30 students enrolled in the fourth semester of the French Language Education Study Program at a university in Bandung, Indonesia, participated in the study. This study used two research instruments to gather the data: a writing assessment consisting of a pre-test and post-test and a questionnaire to measure students' perceptions of the studies' treatment. The data test was analyzed using the CEFR A2-level assessment instrument from Tagliante (2005) and then processed statistically using SPSS 26 software. While questionnaire data were analyzed using a Likert scale with five intervals. The statistical analysis results demonstrated a substantial impact, indicating increased scores from the pre-test to the post-test. The observable augmentation in the caliber and efficacy of student writing across all evaluation domains supports this assertion. In conclusion, the implementation of peer and teacher feedback using Twitter in French as a Foreign Language (FFL) writing class significantly enhances students' writing proficiency. Furthermore, it allows students to demonstrate a favorable acceptance and perception of this implementation to improve their French writing skills.